Punkty kontaktowe jako źródła informacji o zasadach podejmowania i wykonywania zawodów adwokata i notariusza w wybranych krajach Unii Europejskiej - Trela, Anna (Studia Prawa Publicznego, 2025)
This article analyses the functioning of what may be called ‘contact points’ related to the practice of the professions of solicitor and notary. The term ‘contact point’ does not have a single legal meaning; however, they perform various roles, including providing information, facilitating the establishment and pursuit of economic activity, training, advising, and even handling complaints and monitoring violations of the law. The starting point for the discussion is an analysis of the provisions of Directive 2006/123/EC of the European Parliament and of the Council of 12 December 2006 on services in the internal market, which imposes on EU Member States provisions on the functioning of single contact points. By creating appropriate online platforms called points of single contact, Member States are to ensure that service providers are able to complete all the procedures and formalities necessary to take up their activities, in particular, submitting all declarations and notifications, and providing access to applications necessary to obtain authorisation from the competent authorities, including applications for entry in a register, list or database, or applications for registration in professional associations or bodies. The implementation of the obligation under Directive 2006/123/EC is classified as an e-government service and is not standardised. Consequently, in Poland, France and Germany, service providers do have access to the above-mentioned procedures and information, but to varying degrees. The study also points to another type of contact point, namely e-Justice, managed by the European Commission. The final part of the study concerns work on a convention on the legal profession and the potential creation of a new contact point, whose task would be to monitor violations of lawyers’ rights in the EU.